2009
DOI: 10.1007/s11596-009-0425-5
|View full text |Cite
|
Sign up to set email alerts
|

Construction of bioartificial renal tubule assist device In Vitro and its function of transporting sodium and glucose

Abstract: To explore a new way of constructing bioartificial renal tubule assist device (RAD) in vitro and its function of transporting sodium (Na(+)) and glucose and to evaluate the application of atomic force microscope in the RAD construction, rat renal tubular epithelial cell line NRK-52E was cultured in vitro, seeded onto the outer surfaces of hollow fibers in a bioreactor, and then cultured for two weeks to construct RAD. Bioreactor hollow fibers without NRK-52E cells were used as control. The morphologies of atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Concurrently, most of the Cl − is reabsorbed paracellularly due to the generated electrochemical gradient, although Cl − channels and Cl − ‐coupled transporters also contribute to Cl‐ reabsorption (Planelles, ). NRK‐52E cell line is derived from PT and express Na + /glucose cotransporter (Dong, Chen, He, Yang, & Zhang, ). The epithelium of PT has low transepithelial resistance and is considered a “leaky” epithelium, in which the paracellular resistance is much lower than the transcellular resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, most of the Cl − is reabsorbed paracellularly due to the generated electrochemical gradient, although Cl − channels and Cl − ‐coupled transporters also contribute to Cl‐ reabsorption (Planelles, ). NRK‐52E cell line is derived from PT and express Na + /glucose cotransporter (Dong, Chen, He, Yang, & Zhang, ). The epithelium of PT has low transepithelial resistance and is considered a “leaky” epithelium, in which the paracellular resistance is much lower than the transcellular resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, most of the Cl − is reabsorbed paracellularly due to the generated electrochemical gradient, although Cl − channels and Cl − -coupled transporters also contribute to Cl-reabsorption (Planelles, 2004). NRK-52E cell line is derived from PT and express Na + /glucose cotransporter (Dong, Chen, He, Yang, & Zhang, 2009).…”
Section: Yeste Et Almentioning
confidence: 99%
“…Some earlier studies suggested or applied bioreactors where renal cells were also seeded on the outer surfaces of HFM . Probably some of the specific advantages of using this configuration were not obvious in these studies, and this might be one reason why this configuration was not widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Tsuruoka et al reported a renal assist device (RAD) using an immortalized proximal tubular cell line for digoxin and doxorubicin removal [107]. More commonly, the RAD was developed to assess the differentiated tubular functions such as water and glucose reabsorption as well as vitamin D activation [108][109][110][111]. RAD normally consisted of a hollow fiber reactor and two circulations of culture medium (Fig.…”
Section: Membrane-based Cell Model In Renal Excretion Of Drugsmentioning
confidence: 99%